Elucidating the pharmacological foundations and mechanisms of the Sihai Shuyu formula in treating Graves’ disease through integrated serum metabolomics and network pharmacology with molecular docking techniques - Xiaoju Liu; Xingjia Li; Wenbin Huang; Yifan Cui; Fengyun Cheng; Guofang Chen; Guofang Chen; Xiaodong Mao; Chao Liu; Chao Liu; Shuhang Xu (Frontiers in Endocrinology)
Ethnopharmacological relevanceThe Sihai Shuyu Formula (SHSY) shows promising potential for treating Graves’ disease (GD), although the therapeutic mechanisms and pharmacological basis of SHSY have not been thoroughly evaluated.ObjectiveThis work is aim to investigate the pharmacological basis and mechanism of SHSY in the treatment of GD by integrating non-targeted serum metabolomics and network pharmacology coupled with molecular docking technology.Materials and methodsGD was induced in mice through injections of Ad-TSH289. Treatments included methimazole, inorganic iodine, and both low and high doses of SHSY administered via gavage. At the end of the treatment period, serum levels of thyroxine (T4) and thyrotropin receptor antibody (TRAb) were measured. Hematoxylin-Eosin (H&E) staining assessed the effects of these pharmacological interventions on thyroid gland tissues. Ultra-High Performance Liquid Chromatography with Quadrupole Time-of-Flight Mass Spectrometry (UPLC-Q-TOF-MS) was used in conjunction with network pharmacology and molecular docking to identify and predict SHSY’s active chemical components and targets. A comprehensive analysis of the multi-level bioinformatic analysis, including protein-protein interactions (PPI) and functional pathways of the targets, was conducted, followed by verification through immunohistochemistry (IHC) to clarify SHSY’s pharmacological basis and action mechanisms in treating GD.ResultsAfter 8 weeks of treatment, SHSY significantly reduced serum T4 and TRAb levels in GD mice and enhanced the morphology of thyroid tissues. Comparative analysis of rat blood samples and SHSY using UPLC-Q-TOF-MS identified 19 blood-entry components, the potential active components of SHSY acting on GD. Further network pharmacological analysis indicated that SHSY targets the PI3K/Akt signaling pathway through components such as PIK3CD, SRC, PIK3CA, HRAS, EGFR, PIK3R1, AKT1, PTPN11, and PIK3CB. Molecular docking confirmed the effective binding of SHSY’s components to these targets. IHC confirmed that the IGF1R/PI3K/Akt signaling pathway is a significant therapeutic target of SHSY, with key substances including Guggulsterone, Betulinic aldehyde, and Forsythoside H.ConclusionsSHSY appears to effectively treat GD through the IGF1R/PI3K/Akt signaling pathway, with Guggulsterone, Betulinic aldehyde, and Forsythoside H as the critical pharmacological components. It may serve as an adjunctive treatment for GD alongside traditional therapies such as antithyroid medications, surgery, and radioiodine therapy.